Health of the Newborn and Breastfeeding during the COVID-19 Pandemic: A Literature Review - Salvador-Pinos, Carmen Amelia; Martinez, Edson Zangiacomi; Dueñas-Matute, Susana Eulalia; Aguinaga, Rosa Romero de; Jácome, Juan Carlos; Michelena-Tupiza, Stephanie; Cárdenas-Morales, Valheria (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective The present article presents a literature review concerning the microbiota of breast milk and the influence of epigenetics in the susceptibility to COVID-19.Methods A literature review.Results Breastfeeding transfers microbiota, nutrients, diverse white blood cells, prebiotics, hormones, and antibodies to the baby, which provide short- and long-term immunological protection against several infectious, gastrointestinal, and respiratory illnesses. The little evidence available shows that breast milk very rarely carries the SARS-CoV-2 virus, and even in those cases, it has been discarded as the source of contagion.Conclusion The reviewed studies show evidence of a beneficial effect of breastfeeding and highlights its importance on the current pandemic due to the immune reinforcement that it provides. Breastfed individuals showed better clinical response due to the influence on the microbiota and to the nutritional and immune contribution provided by breast milk, compared with those who were not breastfed.
Keywords: breast milk; COVID-19; microbiota; neonate; SARS-CoV-2; bacterial colonization; pregnancy